The Role of Epithelial–Mesenchymal Transition in Malignant Pleural Mesothelioma: From Pathogenesis to Diagnosis and Treatment - Dimitrios E. Magouliotis; Fabrizio Minervini; Ugo Cioffi; Matilde De Simone; Davide Patrini; Marco Scarci (Cells)
Malignant pleural mesothelioma (MPM) is an aggressive cancer of the pleural lining, primarily associated with asbestos exposure. Despite advancements in multimodal treatment, patient survival remains poor. Epithelial–mesenchymal transition (EMT) has emerged as a crucial process driving MPM pathogenesis, metastasis, and resistance to therapy. This review explores the molecular mechanisms underlying EMT in MPM, including key signaling pathways such as TGF-β, Wnt/β-catenin, and PI3K/Akt. We also discuss the diagnostic and prognostic significance of EMT-related biomarkers and emerging targeted therapies aimed at reversing EMT or exploiting EMT-induced vulnerabilities. Additionally, recent clinical trials, including the MARS 2 trial, are reviewed to provide insight into the evolving treatment landscape.